IMPROVING EARLY CHILDHOOD'S ABILITY TO RECOGNIZE THEIR IDENTITY THROUGH THEMATIC LEARNING ON "SELF" - Khabibatul, Muniroh (Journal of Teaching and Education, 2025)
Study This aim For increase ability child age early Group A at RA Al-Ittihad Poncol in know identity self through application of learning models Thematic with theme "Myself " . The background of this study is the finding that most children aged 3-4 years in the class still have difficulty stating their complete personal identity (full name, age, gender, parents' names) and lack confidence in expressing themselves. The study was conducted in two cycles, where each cycle consisted of planning, action implementation, observation, and reflection. The research subjects were 16 children in Group A. Data collection techniques used observation with checklists, anecdotal notes, and documentation. The results of the study showed a significant increase from the initial condition to the end of the cycle. In the initial condition, the ability to recognize children's self-identity was relatively low. After the implementation of Cycle I, there was an increase where most children began to be able to state basic identities, but still needed help and there was a feeling of shame. In Cycle II, after actions that emphasized self-exploration and emotional expression (such as reflecting and telling stories), almost all children showed the ability to recognize their self-identity independently (reaching the expected success limit), as well as significant improvements in fine motor and social-emotional aspects. It is concluded that Thematic Learning with the theme "Self" is effective and relevant as a strategy to develop self-concept and self-confidence in early childhood.